RETRACTED : The Role of Trichoderma sp. as a Biocontrol Agent in Suppression of Root Rot Disease and Soybean Plant Biostimulants - Maknunin, Lu'lu'il; Abadi, Abdul Latief; Choliq, Fery Abdul (University of Brawijaya, 2025)
This article has been retracted at the request of the author. The author has published the article in the Jurnal Fitopatologi Indonesia (JFI).